2017
DOI: 10.1002/cre2.60
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adjunctive effect of 0.1% sodium hypochlorite mouthwash combined to full‐mouth ultrasonic debridement on supragingival plaque, gingival inflammation, and subgingival microbiota: A randomized placebo‐controlled 6‐month trial

Abstract: To test the adjunctive effect of 0.1% sodium hypochlorite (NaOCl) mouthwash combined to full‐mouth ultrasonic debridement (FMUD) on reducing supragingival plaque, gingival inflammation, and microbial pathogens. In this 6‐month double‐blinded randomized clinical trial, individuals with gingivitis were assigned to test (n = 16) or placebo group (n = 16) and received FMUD followed by rinsing with 0.1% NaOCl (test) or distilled water (placebo), respectively, twice a day for 1 month. Full‐mouth periodontal examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The fact that one of the three comparisons with a negative control (II 28 ) included in this systematic review showed no additional benefits of NaOCl‐MW on plaque and periodontal parameters can presumably be explained by differences in NaOCl concentrations, study design, periodontal condition of the participants selected for the study, as well as usage, frequency and duration of rinsing with the anti‐microbial mouthwash. Among the brushing studies that included patients with gingivitis, Espindola et al (II 28 ) used the lowest concentration 0.1%, as recommended by the American Dental Association (ADA). The other two studies, III 27 and IV 25 used a 2.5 and 5 times higher concentration, respectively, and in study IV, 25 the patients used the mouthrinse for a duration twice as long.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The fact that one of the three comparisons with a negative control (II 28 ) included in this systematic review showed no additional benefits of NaOCl‐MW on plaque and periodontal parameters can presumably be explained by differences in NaOCl concentrations, study design, periodontal condition of the participants selected for the study, as well as usage, frequency and duration of rinsing with the anti‐microbial mouthwash. Among the brushing studies that included patients with gingivitis, Espindola et al (II 28 ) used the lowest concentration 0.1%, as recommended by the American Dental Association (ADA). The other two studies, III 27 and IV 25 used a 2.5 and 5 times higher concentration, respectively, and in study IV, 25 the patients used the mouthrinse for a duration twice as long.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the patients in these studies (III 27 and IV 25 ) were instructed not to drink or eat for 30 min after rinsing, which means that the anti‐microbial agent could be present in the mouth for a longer period. Considering the outcome, it is likely that the ADA‐recommended concentration of 0.1% NaOCl does not provide the best anti‐microbial effect against the microflora related to periodontal disease, which may explain the findings reported by Espindola et al (II 28 ). However, comparison V 39,40 used a 2.5 times higher NaOCl concentration, but participants used the mouthrinse only twice a week.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations